Characterization of socioeconomic status of Japanese patients with atopic dermatitis showing poor medical adherence and reasons for drug discontinuation. Issue 3 (September 2015) - Murota, Hiroyuki; Takeuchi, Satoshi; Sugaya, Makoto; Tanioka, Miki; Onozuka, Daisuke; Hagihara, Akihito; Saeki, Hidehisa; Imafuku, Shinichi; Abe, Masatoshi; Shintani, Yoichi; Kaneko, Sakae; Masuda, Koji; et al.
Highlights Adherence level in1327 Japanese subjects with atopic dermatitis was assessed with Morisky Medication Adherence Scale-8. Medication adherence level in Japanese subjects with atopic dermatitis was relatively low compared with that of other chronic diseases. The socioeconomic status of patients with poor adherence was characterized.